2021
DOI: 10.1016/j.jpeds.2020.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease and Clinical Outcome Disparities Among Black Children

Abstract: Study design ICD codes were used to identify children with Kawasaki disease admitted to a tertiary Southeast U.S. center. Subjects diagnosed and treated according to AHA criteria were included. Demographic, laboratory, clinical and echocardiographic data from EMR (2000-2015) were compared between Blacks and Whites. Results Data from 369 subjects (52% Whites and 48% Blacks) were included in our analysis. No significant differences related to timely admission, IVIG treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…An epidemiological investigation in Jilin Province shows that the incidence of male children is 1.83 times higher than that of female children (20). At present, the incidence of Kawasaki disease in male children is higher than that in female children in most studies, but there is no significant difference in coronary artery disease between the male and female children in some reports (21)(22)(23). Haijian et al (24) found that the male-to-female ratio of children with Kawasaki disease aged less than 6 months can reach 9:1.…”
Section: Discussionmentioning
confidence: 96%
“…An epidemiological investigation in Jilin Province shows that the incidence of male children is 1.83 times higher than that of female children (20). At present, the incidence of Kawasaki disease in male children is higher than that in female children in most studies, but there is no significant difference in coronary artery disease between the male and female children in some reports (21)(22)(23). Haijian et al (24) found that the male-to-female ratio of children with Kawasaki disease aged less than 6 months can reach 9:1.…”
Section: Discussionmentioning
confidence: 96%
“…Even the incidence in American children of Japanese or African American descent significantly exceeds that of Caucasian descent ( 64 ). Compared with Caucasian children, African American children with KD have more severe inflammation and extended hospitalizations ( 65 ). Previous reports attributed these racial disparities to differences in socioeconomic and environmental factors ( 66 ).…”
Section: Racial and Ethnic Disparitiesmentioning
confidence: 99%
“…Ethnic or regional differences in treatment response are difficult to discern from literature due to practice variations and often unclear or divergent definitions for outcome parameters including IVIG resistance. Some studies show that children with Hispanic or African American ancestry demonstrate higher rates of IVIG resistance than comparable populations with European or East Asian ancestry ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%